Relation between Lipid Profile and Total Antioxidant Status among Normal Population - Gupta, N.; Khadka, P.; Yadav, S. (Journal of Nepal Chemical Society, 2012)
This study was conducted to assess serum lipids in normal people in relation with their total antioxidant status. Altogether 50 fasting blood samples were collected for study in age between 20-50 years. Fasting lipid profile was determined with enzymatic method i.e. triglyceride (TG), high density lipo-protein (HDL) and low density lipo-protein (LDL) whereas total cholesterol (TC) by chemical method using FeCl3 reagent. The antioxidant status was determined by Ferric Reducing Ability of Plasma (FRAP) assay using TPTZ solution. The statistical analysis was done by SPSS program using Pearson’s correlation coefficient. TG showed negative significant correlation with total antioxidant status (p<0.01) and HDL showed positive significant correlation (p<0.05). Whereas TC and LDL showed non-significant correlation with total antioxidant status (p>0.05). DOI: http://dx.doi.org/10.3126/jncs.v27i1.6440 J. Nepal Chem. Soc., Vol. 27, 2011 53-60 Uploaded date: 16 July, 2012